2022
DOI: 10.3389/fvets.2022.855164
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporin A Prevents Ovarian Graft Rejection, and Permits Normal Germ Cell Maturation Within the First 5 Weeks Post-transplantation, in the Domestic Turkey (Meleagris gallopavo)

Abstract: Biobanked ovaries collected from recently hatched poults can only be revived through transplantation, using a recipient bird. The main hurdle in transplantation is preventing graft rejection, which appears as lymphocytic infiltration upon histologic evaluation of the graft. In this study, the condition of the transplants [immunological compatibility (auto- vs. allotransplants), donor age, time in holding media, and temperature of holding media] and treatment of recipient poults with varying immunosuppressants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…In addition, it was demonstrated that nonimmunosuppressed hosts could produce progeny derived from a donor-ovarian graft ( Song and Silversides, 2007b ). The same inhibitor of T- and B-cell proliferation was used to evaluate its efficiency in suppressing the immune response of a turkey recipient against a turkey ovarian graft of similar background ( Hall et al, 2022a ). This immunosuppressor, used at the same concentration in a turkey host, could not block the infiltration of immune cells into the graft.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was demonstrated that nonimmunosuppressed hosts could produce progeny derived from a donor-ovarian graft ( Song and Silversides, 2007b ). The same inhibitor of T- and B-cell proliferation was used to evaluate its efficiency in suppressing the immune response of a turkey recipient against a turkey ovarian graft of similar background ( Hall et al, 2022a ). This immunosuppressor, used at the same concentration in a turkey host, could not block the infiltration of immune cells into the graft.…”
Section: Discussionmentioning
confidence: 99%